Interpretative phenomenological analysis theory, method and research - Smith, Jonathan A. (Sage Publications, 2009)
This title presents a comprehensive guide to interpretative phenomenological analysis (IPA) which is an increasingly popular approach to qualitative inquiry taught to undergraduate and postgraduate students today.